Per-oral pancreatoscopy with intraductal lithotripsy for difficult pancreatic duct stones: a systematic review and meta-analysis - McCarty, Thomas R.; Sobani, Zain; Rustagi, Tarun (Endoscopy International Open, 2020)
Background and study aims Per-oral pancreatoscopy (POP) with intraductal lithotripsy via electrohydraulic lithotripsy (EHL) or laser lithotripsy (LL) facilitates optically-guided stone fragmentation of difficult pancreatic stones refractory to conventional endoscopic therapy. The aim of this study was to perform a systematic review and meta-analysis to evaluate the efficacy and safety of POP with intraductal lithotripsy for difficult pancreatic duct stones.Methods Individualized search strategies were developed in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses and Meta-analysis of Observational Studies in Epidemiology guidelines. This was a cumulative meta-analysis performed by calculating pooled proportions with rates estimated using random effects models. Measured outcomes included pooled technical success, complete or partial stone fragmentation success, complete duct clearance after initial lithotripsy session, and adverse events (AEs).Results Ten studies (n = 302 patients; 67.72 % male; mean age 55.10 ± 3.22 years) were included with mean stone size of 10.66 ± 2.19 mm. The most common stone location was in the pancreatic head (66.17 %). Pooled technical success was 91.18 % with an overall fragmentation success of 85.77 %. Single lithotripsy session stone fragmentation and pancreatic duct clearance occurred in 62.05 % of cases. Overall, adverse events were reported in 14.09 % of patients with post-procedure pancreatitis developing in 8.73 %. Of these adverse events, 4.84 % were classified as serious. Comparing POP-EHL vs POP-LL, there was no significant difference in technical success, fragmentation success, single session duct clearance, or AEs (P > 0.0500).Conclusions Based on this systematic review and meta-analysis, POP with intraductal lithotripsy appears to be an effective and relatively safe procedure for patients with difficult to remove pancreatic duct stones.